Implementasi Artificial Intelligence (AI) Dalam Pembentukan Peraturan Perundang-Undangan Di Indonesia (International Forum of Researchers and Lecturers, 2024)
The aim of this study is to find out how to implement the use of Artificial Intelligence (AI) in the formation of laws and regulations in Indonesia. This study uses a normative juridical method with a statutory and regulatory approach as well as secondary legal materials, namely books on Legislation, other books related to this case and scientific journals from previous research. The study results show that Al can still be utilized in the process of forming regional regulations without eliminating or even replacing the role and function of the regional regulation forming organs. The use of AI in the process of forming regional regulations is only limited to tools that can be used during the harmonization process in the stages of drafting regional regulations. The use of AI is said to have better accuracy and speed in predicting potential disharmony between regional regulations and various other laws and regulations.